Modelling of chlorine residual in the water distribution network at Bukit Tunku, Kuala Lumpur - Ying-Chyung, Foong; Ghazaly Shaaban, Md.; Othman, Faridah (Malaysian Journal of Science, 2004)
The purpose of this study was to investigate the fate of the residual chlorine in the water distribution system. Network simulation model was developed using EPANET 2.0 software to investigate and compare two commonly used chlorine decay models which is single decay coefficient and the combined bulk and wall demand model. A study area at Bukit Tunku, Kuala Lumpur was chosen based on the public complaints data on the degradation of water quality provided by PUAS Berhad. Fifteen samples were taken from the treated water exit at Bukit Nanas Water Treatment Plant and the residual chlorine was tested daily. The bulk decay constant was determined from the experiment to be —0.312/d. And, the wall decay coefficient which determined by trial and error from the model was —0.91 m/d. From the model result, the decay coefficient was clearly shown to be varying at different pipe section and the system demand of chlorine was higher than bulk chlorine demand.